Ground-borne noise and vibrations in buildings induced by pile driving: An integrated approach. (August 2021) - Colaço, A.; Alves Costa, P.; Mont'Alverne Parente, C.; Silva Cardoso, A.
Abstract: The use of pile driving techniques in urban environments demands accurate methods to predict and mitigate the potential discomfort of residents of neighboring buildings. In this context, a numerical model to predict ground-borne noise and vibrations in buildings induced by pile driving is proposed in the present paper. The model is based on a sub-structuring approach, in which the entire propagation medium is considered, from the vibration source to the receiver. The pile-ground domain is simulated by an equivalent linear FEM-PML approach formulated under axisymmetric conditions taking into account the pile-hammer interaction. The building simulation is performed using a 3D FEM approach, adequately adapted to include the soil-structure interaction, while the acoustic field induced by the structural vibration is analysed using a 3D MFS model. The levels of ground-borne noise and vibration inside the building resulting from pile driving are assessed through an application example, clearly showing the potential of the proposed methodology.